An Ethnomusicological Study of the Traditional Songs of the Chisasibi Cree - Whidden, Lynn (Université de Montréal, 1986)

Les hymnes, une anomalie parmi les chants traditionnels des Cris du Nord - Whidden, Lynn (Recherches amérindiennes au Québec, 1985)

Hymn Anomalies in Traditional Cree Song - Whidden, Lynn (Recherches amérindiennes au Québec, 1987)

Un projet d'éducation musicale à Wemindji, Québec - Whidden, Lynn (Recherches amérindiennes au Québec, 1985)

Essential Song: Three Decades of Northern Cree Music - Whidden, Lynn (Wilfrid Laurier University Press, 2007)
A pack that contains a book and a CD. The book presents an outline of Cree musical history and a contribution to ethnomusicology, social history, and Aboriginal studies. The CD contains over 80 Cree hunting songs.

Traditional Cree Song and the Problem of Creativity in Music - Whidden, Lynn (Actes du quatorzième congrès des algonquinistes, 1983)

"Gnaah" and the Trout Song - Whidden, Lynn (Proceedings of Eighth Workshop on the Structure and Constituency of Languages of America, 2003)